Produksi tanaman pakcoy (Brassica rapa) pada tiga jenis kombinasi pupuk organik cair kototran lele - Milawati Lalla; M. Iqbal Jafar; Pranoto Pranoto (Jurnal Agercolere, 2022)
Catfish manure, goat manure, cow urine and lamtoro leaves are organic materials that are easily obtained and have not been used optimally. To utilize this material, it can be made into liquid organic fertilizer to make it easier to apply and make combinations in order to increase the growth pakcoy plants significantly. The aim of the study was to obtain a combination of organic materials that gave the best results on pakcoy plants. This field research was arranged based on the Randomized Block Design consisting of 4 treatments and 4 replications using a plot measuring 1 m², a spacing of 20 cm x 20 cm. The treatments were P0= catfish manure (control), P1= catfish manure + goat manure, P2= catfish manure + cow urine and P3= catfish manure + lamtoro leaves. The observed variables were the number of leaves, fresh weight harvested, root length and root weight. The results showed that catfish manure and goat manure (P1) significantly increasing the number of leaves, fresh harvest weight and root weight of pakcoy plants.